Influence of Individual Characteristics and Development Career Towards Employee Loyalty at PT. Satria True Food Tuban-Kuta - Yohana, Sandeng; Made, Yudhaningsih Ni; Kadek, Donny Wishanesta I (International Journal of Management and Business Intelligence, 2024)
Humans have an important role in today's globalized world. Human resources are an important resource in the company. It cannot be denied that an organization develops and progresses if the HR management element contributes a significant influence to the future. The phenomenon that occurs in this research is that employee development experiences change every year, namely the number of employees rises and falls very rapidly, thus affecting the performance of these employees. This research aims to determine the influence of individual characteristics and career development on PT employee loyalty. True Food Warriors. The population in this study used all employees, namely 150 employees with a sample of 60 people. This type of quantitative research was used in this research and the data processing tool was assisted by SPSS.  The research results show that individual characteristics contribute a negative and insignificant influence on employee loyalty, then career development also has a significant positive influence on employee loyalty, and individual characteristics and career development have a positive and significant influence on employee loyalty. The company holds an activity to improve employee attitudes and behavior in this case by holding training, evaluations, and also providing motivation to employees so they can improve their performance better.